Literary intelligence : a virtue theoretical analysis with special reference to its educational implications - Peperstraten, Jan-Jaap van (LUP Dissertaties., 2010)
Many arguments have been made for the moral relevance of reading capacity. In this study Jan-Jaap van Peperstraten focuses on the most viable of these: the notion of a 'Literary Intelligence' as formulated by the English literary critic F.R. Leavis and his students. It is argued that Literary Intelligence is best conceptualized as a form of intellectual virtue: an acquired, intrinsically good, cognitive mental trait. Particular recourse is taken to the virtueethical work of Linda Trinkaus Zagzebski and it is concluded that the fostering of a reading praxis may lead to the cultivation of the in.